Discovery of novel isoliquiritigenin analogue ISL-17 as a potential anti-gastric cancer agent - Huang, Fengchang (Biosci Rep, 2020)
Isoliquiritigenin (ISL), a natural product isolated from licorice root, exhibits anti-gastric cancer effects. However, applications of ISL are still limited in clinical practice due to its poor bioavailability. To discovery of more effective anti-gastric cancer agents based on ISL, aldol condensation reaction was applied to synthesize the ISL analogues. MTS assay was used to evaluate the inhibitory activities of ISL analogues against SGC-7901, BGC-823 and GES-1 cells in vitro. Cell cycle distribution, apoptosis and reactive oxygen species (ROS) generation were detected by flow cytometry. Western blot assay was used to analyze the expression levels of related proteins. The drug-likeness and pharmacokinetic properties were predicted with Osiris property explorer and PreADMET server. As a result, 18 new ISL analogues (ISL-1 to ISL-18) were synthesized. Among these analogues, ISL-17 showed the strongest inhibitory activities against SGC-7901 and BGC-823 cells, and could induce G2/M cell cycle arrest and apoptosis in these two cell lines. Treatment with ISL-17 resulted in increased ROS production and elevated autophagy levels in SGC-7901 cells. The PI3K/AKT/mTOR signaling pathway was down-regulated after treatment with ISL-17 in SGC-7901 cells. The results of drug-likeness and pharmacokinetic prediction indicated that all the ISL analogues complied with Lipinski's rule of five and Veber rule and had a favorable ADME character. Overall, our results attest that ISL-17 holds promise as a candidate agent against gastric cancer.